THEMATICALLY CHARACTER-BASED LEARNING MATERIALS IN EARLY CHILD EDUCATION: A PRELIMINARY - Susany Somantri, Annie; Noviantoro, Nuriska; Rahma Ghoer, Fadila (PEOPLE: International Journal of Social Sciences, 2017)
Character education has become a reference for the development of learning patterns of schools in Indonesia. The development of classroom learning instructions integrating character education has been applied in a variety of interesting teaching and learning patterns, despite not all of them being capable of promoting character education appropriately. In its capacity as a reference for learning, learning materials should be able to act as a basic guideline which is to be further developed by teachers in the learning environment. This study aims to identify the needs of PAUD teaching materials in PAUD institutions in West Java and to find teaching materials that had been and are being used in PAUD institutions in West Java. The subjects of the study were three PAUD institutions in West Java selected based on the accreditation of BAN PNF West Java. The instruments used were document analysis, questionnaire, and observation. From the interim results, it was found that the teaching materials used still has not integrated thematic learning in a friendly character education environment. Initial needs analysis of the thematically character-based materials shows that teachers still do not understand in detail about the characteristics of a well-designed thematically character-based learning materials. The teacher's knowledge of evaluating teaching materials has not been able to support teachers' understanding on how the thematically character-based learning materials were developed integrated with character education, whether in the forms of direct instruction, games, or assignments. Related to teaching materials that had been and are being used, there are differences of understanding where an institution have begun to evaluate and integrate the vision and mission of the institution with the vision and mission of national education and other two institutions regard textbook as a standard reference on how the learning process should take place.